A case report of ruptured corpus luteal cyst with congenital bleeding disorder - Dohare, Rubina; Tiwari, Surbhi; Roy, Somlina (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Women of reproductive age with Von Willebrand disease (VWD) are at increased risk of haemorrhagic ovarian cysts due to excessive bleeding into the corpus luteum during ovulation. The rupture of these cysts can lead to life-threatening hematoperitoneum and other complications such as pelvic adhesions, fallopian tube blockages, and ovarian damage, which may impair fertility. Early diagnosis and management of VWD are critical to mitigating these risks. A 20-year-old unmarried woman presented to the emergency department with acute abdominal pain and vomiting. She was hemodynamically unstable and in shock, with severe pallor, abdominal distension, and guarding. Laboratory tests revealed a hemoglobin level of 3.9 g/dl. Imaging suggested a ruptured corpus luteal cyst with gross haemoperitoneum, and a negative urine pregnancy test ruled out ectopic pregnancy. Emergency laparotomy revealed a ruptured 4x2 cm corpus luteal cyst and approximately 2000 cc of haemoperitoneum, which was drained. Postoperatively, the patient experienced recurrent bleeding from the wound site, requiring multiple blood transfusions, resuturing, and a second exploratory laparotomy to drain a 500 cc subcutaneous hematoma. Further investigations confirmed a diagnosis of VWD. The patient was managed with transfusions of blood products and factor VIII and eventually discharged in stable condition. This case underscores the diagnostic and therapeutic challenges of managing VWD in reproductive-aged women with acute gynecological emergencies. Severe haemoperitoneum, recurrent bleeding, and impaired wound healing necessitate a high index of suspicion for bleeding disorders in similar presentations. Multidisciplinary care involving gynecologists, hematologists, and critical care specialists is essential for optimal outcomes.